1)(2x-1)(x-2)=5(x-2)^2 2)x^2+2x=16x-49 Если можно с полным решением:)
1)(2x-1)(x-2)=5(x-2)^2 2)x^2+2x=16x-49 Если можно с полным решением:)
Ответ(ы) на вопрос:
1)(2x-1)(x-2)=5(x-2)^2 2x^2 - 4x - x +2=5(x^2 - 4x+4) 2x^2 - 4x - x+2= 5x^2 - 20x+20 2x^2 - 4x - x+2 - 5x^2+20x - 20=0 -3x^2+15x - 18=0 (делим на ( -1) ) 3x^2 - 15x+18=0 D=15^2 - 4*3*18= 225-216=9 кореньD=3 x1= (-5+3) / 2*3= -12/6= -2 x2= ( -15 - 3) / 2*3= -18/6= -3 x1= -2 x2= -3 2)x^2+2x=16x-49 x^2+2x - 16x+49=0 x^2 - 14x+49=0 D=14^2 - 4*1*49=196-196=0 x=14+0 / 2=14/2=7 x=7 Удачи!)
Не нашли ответ?
Похожие вопросы